Effect of meta-topolin and kinetin at various concentrations on shoot multiplication in white turmeric (Curcuma zedoaria Rosc.) - Murgayanti, Murgayanti; Azizah, Annisa Nanda Nur; Nuraini, Anne; Suminar, Erni; Mubarok, Syariful (Universitas Padjadjaran, 2025)
White turmeric is a medicinal plant widely used to treat various diseases. The limited availability of white turmeric seedlings is influenced by the scarcity of quality seeds due to the long dormancy of the rhizomes and the high incidence of pathogen attacks. Tissue culture techniques are one alternative to address the problem of white turmeric seedling availability. This study aims to determine the best concentrations of meta-topolin and kinetin for in vitro shoot multiplication of white turmeric. The research was conducted from January to June 2022 at the tissue culture laboratory, Faculty of Agriculture, Universitas Padjadjaran. This study used a completely randomized design consisting of 7 treatments: control (0 mg L-1), meta-topolin (1 mg L-1; 2 mg L-1; 3 mg L-1), kinetin (1 mg L-1; 2 mg L-1; 3 mg L-1). Analysis of variance (ANOVA) and Duncan’s multiple range test were used to analyze the statistical effects of meta-topolin and kinetin application. Applying 1 mg L-1 meta-topolin yielded the best results for shoot number, indicating that 1 mg L-1 meta-topolin is a potential cytokinin for the propagation of Curcuma zedoaria Rosc.